Terapi Musik Menurunkan Tingkat Depresi pada Lansia di Panti Sosial: Kajian Literatur - Sahda Eka Ardiyanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The elderly who live in social institutions are more at risk of depression than the elderly who live with their families. Because the elderly have no place to complain. Depression is often overlooked and triggers suicide. Generally, depression is given pharmacological therapy, namely anti-depressant drugs. However, these drugs have side effects and if not consumed regularly, they will cause symptoms of recurrence. For this reason, non-pharmacological therapy is needed to reduce depression, namely music therapy. Music can increase serotonin which causes feelings of happiness. The purpose of this literature review is to explain the effect of music therapy on reducing depression levels in the elderly living in social institutions based on the literature sources of related scientific research journals. The method used was a search for articles on Google Scholar using the keywords music therapy, elderly, depression, and social homes. Then the articles were selected using PRISMA. Then the data obtained were systematically organized and discussed. Music therapy is effective for reducing depression in the elderly in social institutions. There are no restrictions in doing music therapy, so this therapy can be applied to all patients.